2014
DOI: 10.1097/paf.0b013e3182887804
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of a Fatal Intoxication by Nucynta

Abstract: Tapentadol (Nucynta) is a centrally acting opioid analgesic prescribed for the treatment of moderate to severe acute pain. Its efficacy is believed to be due to μ-opioid receptor agonist activity and inhibition of norepinephrine reuptake resulting in increased norepinephrine concentrations. There is only one other case in the literature relating to the toxicity of this agent or report of a fatality. This case report documents a case in which tapentadol was identified as the cause of death. The tapentadol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…A study by Dart et al found that rates of drug abuse with intermediate release tapentadol were low during the first 24 months after its launch [ 15 ]. Published reports of lethal tapentadol overdoses include a case report by Franco et al, which describes a patient death attributed to tapentadol intoxication, possibly leading to respiratory depression, central nervous system depression, and serotonin syndrome [ 16 ]. Another published case reported by Kemp et al described a patient death following intravenous injection of tapentadol [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dart et al found that rates of drug abuse with intermediate release tapentadol were low during the first 24 months after its launch [ 15 ]. Published reports of lethal tapentadol overdoses include a case report by Franco et al, which describes a patient death attributed to tapentadol intoxication, possibly leading to respiratory depression, central nervous system depression, and serotonin syndrome [ 16 ]. Another published case reported by Kemp et al described a patient death following intravenous injection of tapentadol [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causes of seizures, after tramadol exposure, are unclear, although some studies, using different models, have associated tramadol antidepressant activity with seizures (Reeves and Cox, ; Reichert et al., ). Besides the adverse reactions discussed so far, more severe toxicological effects, with even more serious implications, have been reported, including respiratory depression, serotonin syndrome (Sansone and Sansone, ; Pilgrim et al., ; Beakley et al., ) and fatal intoxications (Tjaderborn et al., ; Pilgrim et al., ; Larson et al., ; Costa et al., ; Kemp et al., ; Pinho et al., ; Franco et al., ; Cantrell et al., ).…”
Section: Toxicitymentioning
confidence: 99%
“…Pulmonary alterations (namely pulmonary oedema) were also reported in a case of tapentadol and oxycodone intoxication, where tapentadol concentrations reached 1.1 mg/L in peripheral blood, 1.3 mg/L in central blood, 9.9 mg/kg in the liver, 0.94 mg/L in vitreous humour, and 88 mg/L in urine (Cantrell et al., ). Another fatal intoxication by tapentadol was reported by Franco et al., who suggested its acute ingestion; the events responsible for death included respiratory and CNS depression and serotonin syndrome, with tapentadol concentration in cardiac blood being as high as 6600 ng/mL, more than 20 times the higher limit of its therapeutic range (Franco et al., ). These authors also reported autolytic changes in kidney, suggestive of tapentadol nephrotoxicity (Franco et al., ).…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although tramadol and tapentadol are claimed to have better safety profiles than their opioid peers, several adverse events have been reported, including nausea, vomiting, dizziness, seizures, dyspnea, respiratory depression [ 1 , 2 , 14 , 47 , 48 , 49 , 50 , 51 ], and even fatal cases [ 10 , 42 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. In the VigiBase™ World Health Organization (WHO) Global Database of Individual Case Safety Reports concerning 5-HT toxicity, tramadol ranks 1st and tapentadol ranks 3rd (with 647 and 115 cases out of 1641, respectively) as the only suspected cause or amongst other drugs, and 1st and 2nd (with 62 and 42 cases out of 147, respectively) as the only suspected cause [ 34 , 69 ].…”
Section: Introductionmentioning
confidence: 99%